On history and policy: time in the age of neoliberalism - Boldizzoni, Francesco (Köln, 2013)
"It is often said that history matters, but these words are often little more than a hollow statement. In the aftermath of the Great Recession, the view that the economy is a mechanical toy that can be fixed using a few simple tools has continued to be held by economists and policy makers and echoed by the media. The paper addresses the origins of this unfortunate belief, inherent to neoliberalism, and what can be done to bring time back into public discourse."